Hybrid Stegnography using ImagesVaried PVD+ LSB Detection Program (International Journal of Engineering and Computer Science, 2015)
Image Stegnography can be achieved by two techniques i.e LSB and PVD. In LSB technique it provide high capacity and good quality but it can be detected very easily by human eye. In other technique PVD, it usually provide less capacity and higher distortion but it can not detected by human eye. So, in this paper I combine the advantages of both the technique and with this I get with the result of higher capacity , low distortion and secrete data will not be detected very easily by human eye.